Pengaruh Social Media Marketing terhadap Customer Engagement dan Brand Loyalty di Zalora Indonesia - Rini, Ramadhani Laila Puspa; Hasbi, Imanuddin (Universitas Batanghari Jambi, 2024)
Problems regarding Zalora Indonesia's Instagram social media marketing are the background for this research. Followers after visiting the Zalora Indonesia Instagram account tend to be less interested in making purchases. This is related to the decline in brand loyalty among consumers, as can be seen from data on visits to Zalora Indonesia from the third quarter to the fourth quarter of 2022. This research aims to find out how social media marketing influences customer engagement and brand loyalty on Zalora Indonesia's Instagram. The method used in this research is quantitative with descriptive and causal types. There were 400 respondents in this study using a non-probability sampling technique, purposive sampling type. Descriptive analysis techniques and path analysis. The research results concluded that social media marketing had a significant influence on customer engagement of 61.6%. Customer engagement has a significant influence on brand loyalty of 9.1%. Social media marketing has a significant influence on brand loyalty of 25.5%; and social media marketing has an indirect influence on brand loyalty through customer engagement of 23.7%.